Investigating the use of medicines in management of children and young people with epilepsy using data from primary care in the UK - Ali, Mostafa (2012)
Background: Epilepsy is a serious chronic neurological disorder that has a higher incidence in children and young people (CYP) than in adults. Epilepsy negatively impacts physical and psychosocial quality of life of CYP. Good outcomes of epilepsy are associated with optimal choice of drug treatment and adequate adherence to the prescribed medicines. Research on the patterns of medication use and adherence to prescribed medicines in CYP remains limited. The long-term clinical outcomes and costs of treating epilepsy have not been extensively studied in CYP in the UK. Aim of the study: This thesis aimed to investigate the pattern of antiepileptic drug (AED) prescribing and the dynamic of medication adherence in CYP with epilepsy. The long-term clinical outcomes and direct costs of treating epilepsy in CYP were estimated at population level. Methods: This study is an observational cohort study of CYP, age 0-17 years, identified from The Health Improvement Network (THIN) primary care database from the UK between January 1988 and December 2004. Four different analyses were carried out on this cohort. First, a cross-sectional design repeated annually was employed to estimate the incidence and prevalence of epilepsy and the pattern of AED prescribing in this population. Secondly, the long-term adherence to prescribed AEDs was calculated using the medication possession ratio (MPR) method. Applying panel data analysis and the Generalised Estimating Equation (GEE) multivariate regression, factors that may have been associated with adherence to the prescribed AEDs were examined. Thirdly, seizure outcomes in terms of seizure frequency and remission of seizures and potential associated factors were assessed using the method of multiple failure survival analysis. Finally, the direct costs of treating epilepsy in CYP in primary care were estimated and stratified by the number of years after the first recording of epilepsy in THIN data. Results: Of total 528,760 CYP born on or after 1st January 1988 and registered in general practices contributed to THIN until 31st December 2004, 2020 CYP were identified who had a diagnosis of epilepsy, from under 1 up to 16.3 years of age (mean=5.6; SD=4.1). The annual incidence of epilepsy in CYP stratified by calendar years ranged from 44.4 (95% CI=31.9-61.8) to 61.2 (95% CI=50.6 -74.1) per 100,000 person-years. Incidence of epilepsy was significantly higher in children with greater socioeconomic deprivation than those with lower deprivation. Around 60% of CYP with epilepsy were prescribed monotherapy each year. Old AEDs such as carbamazepine and sodium valproate were the most frequently prescribed drugs and often prescribed as monotherapy to control epilepsy throughout 1990-2003. Prescribing of lamotrigine, a new AED, increased from 0.07 per person-years in 1992 to 2 per person-years in 2003. The calculated annual adherence to AEDs showed that around 50% of CYP adhered to at least 80% of the prescribed medications each year. Demographic characteristics of CYP were of little significance to affect adherence levels. The incidence of seizures was 0.73 (95% CI=0.71-0.75) per person-years. Incidence of seizures was higher in younger children up to 2 years and decreased with increasing age. A proportion of 94% (95% CI=93%, 96%) of CYP achieved 1 year remission of seizures, 80% (95% CI= 78%, 83%) achieved 2 years and 47% (95% CI=43%, 50%) achieved 5 years remission of seizures. The mean total direct cost associated with treating epilepsy in CYP, according to information in the general practice records that also indicated specialist and hospital care, was estimated at £ 1,153 (SD=1,808) per child in the first year following epilepsy diagnosis and at £459 (SD=1,633) per child for subsequent years. The costs of hospital care and AEDs represented the highest contribution to the total direct costs of epilepsy. The annual direct cost was significantly higher in younger children up to 2 years old. No significant difference in the annual costs was observed between CYP who adhered to at least 80% of medications and those who adhered to less than 80%. Conclusions: The incidence of epilepsy was highest in young children and CYP of higher socioeconomic deprivation. Old AEDs were most often prescribed as first-line drugs and as monotherapy to control epilepsy. Of newer AEDs, there was an increasing trend of prescribing lamotrigine and topiramate as add-on therapy. Long-term adherence to prescribed AEDs was suboptimal in one-half of CYP and positively associated with higher seizure frequency. Inpatient hospital care and drugs were the major contributors to the direct costs of treating epilepsy in CYP. Non-adherence to prescribed medicines was associated with higher hospital care costs but not with total direct costs as the medicines themselves made large contribution to the direct costs